The Power of thought - Valentine, James Lee (Mandaluyong City, Philippines : National Book Store, 2002)
The MLM POWER series is intended for the personal development of Network Marketers only.
1. Create an empowered state of being -- 2. Positive mental attitudes are the key -- 3. A powerful self-image is so important -- 4. Develop an invincible wining philosophy -- 5. Choose personal excellence for yourself.
Keywords: BEING